The Redesign of Theology of Giving As a Catalyst for Loving Humanity in a Pandemic Era - Susanto, Susilo; Gultom, Joni Manumpak Parulian; Pakiding, Herman (The Faculty of Islamic Theology and Humanities, UIN Walisongo Semarang, Indonesia, 2021)
Theology in Giving greatly influences a person's helping, giving, and sowing wealth. However, the redesign of the theology of giving needs to be emphasised to anticipate primordialism in giving as a catalyst for helping human needs in this pandemic era. The pandemic has taken away human happiness and peace, and increased death rates, poverty, and neglect are happening everywhere. The first question is, how does theology of giving according to the Bible? Second, how does applying the theology of giving become a catalyst in loving humans in the era of the pandemic? The purpose of this study was to find out the truth of the theology of giving based on the Bible and the steps in applying the theology of giving as a catalyst for aid in a pandemic. Qualitative research with a literature study and observation approach. The research results on the theology of giving according to biblical truth are 1. They are giving with love. 2. Give by faith. 3. Giving willingly, sincerely, and joyfully. 4. Give your best, not what's left. 5. Giving in all circumstances. 6. Sow bountifully you will reap; sow will reap little. 7. Giving impacts this world and the life to come. This application of the theology of giving is threefold: teaching, modeling, and organising.